(untitled) (GeoPatterns, 2024)
Sessions related to geoheritage have been held under different convenorships and titles since 2012 at the European Geosciences Union General Assembly in Vienna. 2020 was a special year, since the session was held online. The author participated with a contribution in 2019 and without one in 2020, and it was an occasion to compare a physical session with oral and poster presentations and a splinter meeting to a digital session.